CORRELATION BETWEEN URIC ACID LEVEL WITH BODY MASS INDEX AND HEMATOLOGY PARAMETERS AMONG HYPERURICEMIA PATIENTS - ulfa fitriani; zuraida zulkarnain; enggar wijayanti (Balai Penelitian dan Pengembangan Kesehatan Aceh, 2021)
Hyperuricemia has became the public health issue worldwide. Hematology parameters abnormality is considered to be one of the factors relating the disease such as hyperuricemia. Current study suggest that body mass index (BMI) related to uric acid (UA) levels. The aim of the study was to examine the association between uric acid levels and hematological parameters and BMI among hyperuricemia patients. This was cross sectional study with 50 hyperuricemia patients in Hortus Medicus clinic. Results demonstrate that of the participants, 54% were women but the mean of UA levels was higher in the men (8,41 + 0,80 mg/dL) than in women (7,38 + 0,97 mg/dL). In BMI classified, the mean BMI for men was normoweight, and the women was overweight. The mean of hematology parameters in both of sex were normal range. No significant association were testified between uric acid levels and hemoglobin, hematocrit, erythrocyte, trombocyt, leukocyte and BMI. This study indicate that uric acid has no apparent association with hematology parameters and BMI